Posted by **Maria** on Sunday, November 24, 2013 at 11:28pm.

consider the equations:f(x)=-6x-1 and g(x)=4x^2 Select the solution for (f+g)(x)

A) -6x-1+4x^2

B) -24x^3 - 4X^2

C) -24x^2 - 1

D) -6X -1 - 24X^2

I think the answer is A. Please help

Thursday

March 23, 2017
Posted by **Maria** on Sunday, November 24, 2013 at 11:28pm.

consider the equations:f(x)=-6x-1 and g(x)=4x^2 Select the solution for (f+g)(x)

A) -6x-1+4x^2

B) -24x^3 - 4X^2

C) -24x^2 - 1

D) -6X -1 - 24X^2

I think the answer is A. Please help

Search